2013
DOI: 10.4274/tpa.116
|View full text |Cite
|
Sign up to set email alerts
|

Tüberoskleroz kompleksi tanılı hastalarda epilepsinin özellikleri ve klinik seyri

Abstract: ÖzetAmaç: Tüberoskleroz kompleksinde en sık görülen nörolojik sorun epilepsidir. Bu çalışma, epileptik tüberoskleroz kompleksi tanılı hastaların epilepsi özeliklerini ve klinik seyrini incelemek, epilepsi seyrini etkileyebilecek etmenleri araştırmak amacıyla planlandı. Gereç ve Yöntem: Çocuk Nörolojisi Kliniği'mizde epilepsi nedeniyle 9 ay-10 yıl izlenen, 1-14 (7,5±4,2 ) yaşları arasında 21 tüberoskleroz kompleksi tanılı hasta (11/10: E/K) çalışmaya alındı. Hastalara ait aşağıdaki bilgiler elde edildi: epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
8
1
1
Order By: Relevance
“…In a study performed in our country, it was reported that the age of onset in patients with tuberous sclerosis complex ranged between 3 days and 2,5 years and 76% of the patients were aged one year or younger. In the same study, the most common seizure type was reported to be partial seizure with a rate of 95% and this was followed by infantile spasm and status epilepticus with a rate of 38% (28). Similar to the literature, seizure was observed in 85% of our patients.…”
Section: B Clinical Diagnostic Criteriasupporting
confidence: 78%
“…In a study performed in our country, it was reported that the age of onset in patients with tuberous sclerosis complex ranged between 3 days and 2,5 years and 76% of the patients were aged one year or younger. In the same study, the most common seizure type was reported to be partial seizure with a rate of 95% and this was followed by infantile spasm and status epilepticus with a rate of 38% (28). Similar to the literature, seizure was observed in 85% of our patients.…”
Section: B Clinical Diagnostic Criteriasupporting
confidence: 78%
“…Intellectual development is generally affected; the frequency and time of onset of the seizures has a direct effect on intellectual development. Mental retardation is observed in 50% of patients and this renders control of seizures difficult (13). Twenty-eight (78%) of our patients had some kind of seizure.…”
Section: Discussionmentioning
confidence: 99%
“…The neurologic findings in patients with tuberous sclerosis are mostly in the form of epilepsy. One third of the clinical picture of epilepsy is in the form of infantile spasm, and 69% of this group had their first seizure before the age of one year (13). Intellectual development is generally affected; the frequency and time of onset of the seizures has a direct effect on intellectual development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common findings on MRI are shown in Table 2. [8] et al [14] et al [10] et al [11] et al [12] et al [13] Hypopigmented skin lesions (%) 100…”
Section: Resultsmentioning
confidence: 99%